Post-consolidation process for modifying microscale and mesoscale parameters of 3D printed composite materials - Yudhanto, Arief; Aldhirgham, Alwaleed; Feron, Eric; Lubineau, Gilles (Frontiers in Materials, 2023)
Advancements in additive manufacturing technology (3D printing) have enabled us to fabricate reasonably good parts using continuous fiber-reinforced matrix composites. Unfortunately, most of these 3D-printed composite parts inherently possess a large number of voids originating from the trapped air within and between molten composite beads during the deposition stage. Removing the voids has thus become a key challenge in attempts to apply 3D printed composite parts for fabricating stiff/strong load-bearing structures. Here, we employed a classical process, viz. compression molding, to post-consolidate 3D-printed continuous carbon fiber-reinforced polyamide (CFPA), and to investigate the implications in terms of microscale parameters (void content) and mesoscale parameters (mechanical properties, plasticity, damage) using matrix-dominated lay-up of [±45]2s. We found that the proposed post-consolidation process could reduce the void of 3D-printed CFPA from 12.2% to 1.8%, enhancing the shear modulus and shear strength by 135% and 116%, respectively. The mesoscale analysis shows that, albeit with less ductility, the post-consolidated CFPA laminate was more resistant to damage than the 3D-printed CFPA. Classical compression molding is thus a promising technique for improving the physical and mechanical performances of 3D-printed composites by reducing inherent void built-ups.